Ductile deformation in alumina/silicon carbide nanocomposites - Wu, H; Roberts, S; Derby, B (2010)
A transmission electron microscope study on cross sections obtained from ground and polished surfaces has revealed that ductile deformation is dominated by dislocations in alumina/silicon carbide nanocomposites containing 1, 5 and 10 vol% silicon carbide particles, and by twinning in unreinforced alumina. The dispersed silicon carbide particles in alumina/silicon carbide nanocomposites restrict the motion of dislocations. A dislocation pinning model is used to compare the possible mechanisms of deformation in alumina and the nanocomposites. Cr-fluorescence piezospectroscopy has been used to characterise the residual stress levels in the materials studied. The measured broadening of the Al2O3/Cr3+ fluorescence peak indicates a dislocation density of 7.3-9.7 x1016 m-2 under the indentations in the nanocomposites, whilst the beneath indentations in alumina is 1-2 orders of magnitude smaller.